Estandarización de los procesos productivos en la Empresa Indupalets Cía.Ltda - Novillo López, Lisseth Maribel (2019)
INDUPALETS CÍA.LTDA company dedicated to the production and marketing of European Pallets has an experience of 25 years of operation in the market, starting from that point a work study was carried out in the production line that involves establishing an acceptable standard time of The tasks performed. The main objective is the Standardization of the Productive Processes, this could be achieved by direct observation in the production line of the European pallets, which allowed a situational diagnosis of the company, and the study of times with a stopwatch, which allowed the development of the route diagrams, process flow diagram, operations diagram, application of the SLP (Plant Distribution),and a manual of procedures in the production line of European pallets, obtaining favorable results for the improvement of productivity. The methodology that was applied in the present investigation are the, Method Engineering and the Measurement of work with the study of times. After performing the standardization in this production line, results were obtained, in the current method 249 pallets are manufactured per day, with a standard time of 7 hours, 21 minutes, 39 seconds; With the proposed method we found a total of 284 pallets per day, with a standard time of less than 6 hours, 42 minutes, 59 seconds, the calculation of the standard time includes the Operators' Actuation Factor through the application of the Westinghouse system.